math

posted by .

substitution
4x + 3y = 3
7x - 9y = 6

  • math -

    from the 1st
    3y = 3-4x
    or 9y = 9 - 12x

    now sub that into the 2nd
    7x - (9-12x) = 6
    19x = 15
    x = 15/19

    back into 3y = 3-4x
    3y = 3 - 60/19 = -3/19
    y = -1/19

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    Integrate x/(x^2 + 4) dx via trig substitution and by u=x^2+4 substitution. Show that results are equal. Via trig substitution of x=2 *tan t, I get: 1/2 * tan^-1 (x/2) + c Via u = (x^2 + 4) substitution, I get: 1/2 * ln |x^2 + 4| + …
  2. Math

    1. Explain the advantages and disadvantages of both the substitution method and the elimination method for solving a system. Help please. The only reasons I can think of is because in substitution it might be more difficult cause there's …
  3. calculus

    We're doing indefinite integrals using the substitution rule right now in class. The problem: (integral of) (e^6x)csc(e^6x)cot(e^6x)dx I am calling 'u' my substitution variable. I feel like I've tried every possible substitution, but …
  4. math

    solve each system of equations by substitution. y=3x-9 please help explain how to solve this using substitution.
  5. math

    int 1/ (sq rt (4sec^2 x +4)) dx trigonometric substitution expression: sq rt (x^2-a^2) substitution: x=a sec x identity: sec^2 x -1=tan^2 x
  6. Trigonometric Substitution

    Trigonometric Substitution a. Explain why the substitution x = asin(Theta) guarantees that cos(Theta) is greater than or equal to 0 . b. What sort of restriction must we put on x and a so that the substitution x = asec(Theta)will guarantee …
  7. Calculus 2

    Evalute the integral of x/(x^2+4)dx using u-substitution and then trigonometric substitution. I did this and got (1/2)ln(x^2+4)+C using u-substitution and x^2+4+C using trigonometric substitution. What did I do wrong?
  8. calculus

    Evaluate the following integrals using the given substitutions. (a) (3x^2 + 10x)dx/(x^3 + 5x^2 + 18 , substitution u = x3 + 5x2 + 18; (b)(14x + 4)cos(7x^2 + 4x)dx,substitution u = 7x^2 + 4x.
  9. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.
  10. Mathematics

    Find using substitution: ∫ 1/[x(1+lnx)^2] dx I'm not sure what substitution to use.

More Similar Questions